The consumers perceptions of employer and service brand equity’s: the exploratory and confirmatory factor analysis - Ščiukauskė, Indrė; Romeika, Giedrius; Šarkiūnaitė, Ingrida (Journal of Business Economics and Management, 2024)
While the traditional components of employer brand equity are applied in the context of an organization’s employees, this study sought to assess a hitherto unexplored context – the extent to which employer brand equity impacts on consumers of an organization’s service brand rather than the target audience. The two research objectives were: 1) to identify the specific dimensions of both employer and perceived service brand equities 2) to assess the relationship between them and consumer behavioral intentions. The study was based on quantitative data of 526 respondents, using both Exploratory (EFA), Confirmatory factor analysis (CFA) and structural equation modelling (SEM). The findings confirmed the 3 (employer brand image, reputation, and awareness) and 4 (service brand image, perceived quality, service brand awareness, brand loyalty) factors of employer and service brand equities respectively. The study revealed the employer brand equity significant relationship with service brand equity, but the lack of direct effect on consumers’ behavioral intentions. The research is novel as it assesses the employer brand equity’s impact not only on the service brand’s overall perceived equity, but also on consumers’ behavioral intentions, by examining the impact on two different groups (existing and potential service brand consumers).